2022
DOI: 10.29303/jppipa.v8i3.1589
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Collaborative Flipped Learning Strategy and Socio-cognitive Ability on Students’ Metacognitive Skills

Abstract: The reality shows that instructors and students are having difficulty implementing online science education during the pandemic. The purpose of this study was to determine the effect of collaborative flipped learning (CFL) strategy and socio-cognitive ability on metacognitive skills and self-efficacy in primary school pre-service teachers who were currently enrolled in a Basic Science course. This objective was motivated by the current state of education and teaching, which necessitates the use of technology t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Junior High School Students A study by Bahri and Corebima [26] suggested that students with strong metacognitive skills are better equipped to set goals, select appropriate learning strategies, and regulate their cognitive processes effectively. Moreover, Abbas et al [27] socio-cognitive model emphasized the significance of metacognitive self-regulation in academic achievement, highlighting its role in fostering strategic learning behaviors and enhancing academic performance. Furthermore, Sheffler et al [28] proposed that metacognitive abilities develop progressively throughout adolescence, indicating that students may exhibit a heightened level of metacognitive awareness compared to younger students.…”
Section: Extent Of Metacognitive Skills Amongmentioning
confidence: 99%
“…Junior High School Students A study by Bahri and Corebima [26] suggested that students with strong metacognitive skills are better equipped to set goals, select appropriate learning strategies, and regulate their cognitive processes effectively. Moreover, Abbas et al [27] socio-cognitive model emphasized the significance of metacognitive self-regulation in academic achievement, highlighting its role in fostering strategic learning behaviors and enhancing academic performance. Furthermore, Sheffler et al [28] proposed that metacognitive abilities develop progressively throughout adolescence, indicating that students may exhibit a heightened level of metacognitive awareness compared to younger students.…”
Section: Extent Of Metacognitive Skills Amongmentioning
confidence: 99%